Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1093/jn/130.11.2760
|View full text |Cite
|
Sign up to set email alerts
|

Platycodi Radix Affects Lipid Metabolism in Mice with High Fat Diet–Induced Obesity

Abstract: An aqueous extract of Platycodi radix inhibited the hydrolysis of triolein emulsified with phosphatidylcholine by pancreatic lipase in vitro and it reduced the elevation of rat plasma triacylglycerol level 2-4 h after oral administration of a lipid emulsion containing corn oil. These preliminary results suggested that the aqueous extract of Platycodi radix may inhibit the intestinal absorption of dietary fat by inhibiting its hydrolysis. Therefore, we examined the antiobesity activity of the aqueous extract of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
139
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(149 citation statements)
references
References 12 publications
4
139
0
1
Order By: Relevance
“…The animal experiment showed that the body weight reduction was highly linked with the calorie intake restriction, which is obviously inconsistent with the previous reports. 1,2 We also observed that a cholesterollowering effect was mainly attributed by the reduction of LDL-cholesterol. A beneficial alteration in the hepatic tissues and fecal excretion was also noted.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…The animal experiment showed that the body weight reduction was highly linked with the calorie intake restriction, which is obviously inconsistent with the previous reports. 1,2 We also observed that a cholesterollowering effect was mainly attributed by the reduction of LDL-cholesterol. A beneficial alteration in the hepatic tissues and fecal excretion was also noted.…”
Section: Introductionmentioning
confidence: 78%
“…A lipase inhibitor which reduces fat digestion and thus absorption, is one of widely accepted approaches in decreasing calorie intake. [1][2][3] Simple inhibition of lipid digestion and absorption is a prerequisite, but it is not sufficient for a successful long-term control of obesity. 4 Therefore, a coordinated measure to either reduce the food intake efficiency or promote energy expenditure is desirable to achieve a long-term efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations